In Accuracy of Management Earning Forecast in IPO Prospectuses - Hamid Khaleghi Moghadam; Mahmood Bahramian (مطالعات تجربی حسابداری مالی, 2005)
Companies going public in Iran include a forecast of next year's profit in their prospectuses. Investors use this information for their future decision. Accuracy of the forecast is crucial because it seems to be a credible signal for long-term performance of stocks. In  this  study  we  examine  the  accuracy  of  management  profits forecasts contained in prospectuses of companies newly listing on the Tehran Stock Exchange. For that reason four different forecast error metrics, forecast error, absolute forecast error, squared forecast error and superiority of management forecast are considered. The interesting feature in this paper is the mandatory status of Tehran market for the disclosure of earning forecast in the prospectuses of the companies and the motivation is that there is no previous literature covering forecast earning accuracy. Data set consists of 81 IPOs, which were floated, in the Athens Stock Exchange during March 2000 to February of 2002. In order to test a number of company specific characteristics, for the accuracy of Tehran IPO management earnings forecasts we conduct a regression analysis .We apply a cross sectional model to explain variations in accuracies but it has very weak significant power. Our results suggest that investors are able to anticipate forecast errors at the time of listings. Investigation on independent variables, influencing the forecast accuracy show that three factors named horizon of the IPO' (HOR), Economic Condition (ECON), Age of Firm (AGE) are significant determinants.